RESPONSE OF SOME GROWTH TRAITS OF SUNFLOWER CROP TO PLANTING DISTANCES, TRIFLURALIN AND DATURA ROOT EXTRACT.: RESPONSE OF SOME GROWTH TRAITS OF SUNFLOWER CROP TO PLANTING DISTANCES, TRIFLURALIN AND DATURA ROOT EXTRACT. (Iraqi Journal of Market Research and Consumer Protection, 2026)
A field experiment was conducted in the field of College of Agricultural Engineering Sciences - University of Baghdad during the spring season 2021, aiming to study the effect of Datura root extract and Trifluralin on accompanying weeds and some growth traits of sunflower (Flami variety). The experiment was designed in a randomized complete block design (RCBD) in split-plot arrangement with three replicates. The main plots were the distances between rows (60, 75,90) cm, the subplots consisted of four weed control treatments: (T1) Trifluralin application at rate 2.4 L ha-1, (T2) Datura root extract application at 18 L.ha-1 M (T3) Trifluralin application at 1.2 L.ha-1 + Datura root extract application at 9 L.ha-1 , (T4)  weedy treatment . The distance 60 cm recorded lowest dry weight of weeds (89.93 g.m-2), highest inhibition percentage (55.81%), and highest leaf area index (0.46). The distance 90 cm achieved highest plant height, leaf area, crop dry weight, and stem diameter, reaching 195.09 cm, 754.6 cm-2, 241.55 g.m-2, and 2.53 cm, respectively. The treatment T1 achieved highest of inhibition percentage, plant height, leaf area, leaf area index, dry weight of sunflower plants, and plant stem diameter of 78.37%, 204.29 cm, 805.60 cm-2, 0.43, 265.62 g, and 2.60 cm, respectively. The interaction effect was significant in the traits under study. The distance 60 cm with treatment T1 achieved low weed dry weight 38.68 g.m-2, high inhibition percentage 81.00 %, and high leaf area index 0.51.  the distance 90 cm and T3 achieved high means of plant height, leaf area, dry weight of sunflower plants, and stem diameter, reaching 212.93 cm, 833.90 cm-2, 307.25 g.m-2, and 2.73 cm, respectively. The results confirm the integration between the effect of distance between lines, herbicide, and the extract in improving the crop traits.